Pemanfaatan Digital Dalam Pemasaran Produk Anyaman Rotan Kampung Kreatif Di Perbatasan - Benedhikta Kikky vuspitasari; Yermia Niaga Atlantika; Novianty Novianty (UNIVED Press, 2023)
This article aims to describe the use of digital in the marketing of creative village rattan woven products in the Border. This research is a qualitative descriptive study using purposive sampling method, data collection, researchers using interviews, observations, and documents. The data analysis used in this study consisted of several stages, namely data reduction, data presentation, and drawing conclusions, to determine the validity of the researcher's data using data triangulation techniques. The results showed that not all of the digital marketing strategies were used properly, the use of social media Facebook and Whatsaap were the most widely used tools, besides that marketing strategies could also be seen through the 4P marketing mix where rattan woven products have the uniqueness of different motifs so that the price is also low. adjusting, strategic location because it is located on the border so that traditional promotion facilities are also very effective.